Uma história da odontologia em Sergipe : do ensino à estruturação do “campo” (1925-1975) - Jesus, Danilo Mota de (2018)
This study aimed to analyze the history of the formation of the field and the creation of the dentistry courses in Sergipe from 1925 to 1975. This is a historical research with an approach in Cultural History. The selection of the temporal cut (1925-1975) is justified by the fact that in 1925 the Faculty of Pharmacy and Dentistry of Sergipe was created, and in 1975 (50 years later), Sergipe had its first dentistry course recognized by Ministry of Education. In the development of the research we use printed and digitized documentary sources, in addition to the written sources we also support the bases of oral history, through semi-structured interviews, we still analyze some images that were being raised in the course of the study. During this work we dialogued with the concepts of Civilization Process of Norbert Elias and the concepts of field and capital of Pierre Bourdieu. In order to change the Higher Education framework in Sergipe, President Graccho Cardoso created in 1925 courses in pharmacy and dental surgery, which aimed to open new career paths for Sergipe youth, but the idea was interrupted after the change management. Only in the 1960s, with the creation of the Federal University of Sergipe, was the possibility of creating a dentistry course within the UFS, but intrigues within the field made it difficult to include the course at the new University, only in 1970 the course was created, in 1973 the first-class graduates and in 1975 the course is recognized by the Ministry of Education. The need to create a dentistry course in Sergipe occurred as a social need to strengthen the dental field, which sought to eradicate the activity of practical dentists.